HOW TO PERFORM SAFE RETROGRADE CHRONIC TOTAL OCCLUSION RECANALIZATION - Božinović, Nenad; Perišić, Zoran; Kostić, Tomislav; Apostolović, Svetlana; Maričić, Bojan; Šalinger, Sonja; Veselinović, Ines; Maričić, Tijana; Živković, Milan; Perišić, Jelena (Acta medicae Medianae, 2024)
Chronic total occlusion (CTO) of the coronary artery is defined as more than three-month-old total (100%) anterograde flow obstruction in the native coronary artery.The data show that 7% − 15% of CTOs are treated with percutaneous coronary intervention and that CTO recanalization still represents the cutting edge in percutaneous coronary intervention. Three different techniques for the CTO recanalization have been described in the literature: antegrade wire escalation, antegrade dissection/re-entry, and retrograde. In case of multiple possibilities for selection of collateral channels, the septal group still represents the most common choice in a large number of retrograde CTO interventions because of the lowest major complication rate. Septal perforations are generally not followed by serious complications and usually resolve spontaneously. On the other hand, epicardial collateral channels can be used with a high rate of success and low incidence of procedural complications when revascularization procedures of CTO lesions are performed by experienced interventional cardiologists and high-volume laboratories
Keywords: chronic total occlusion, percutaneous coronary intervention, collateral channels